Literature Review: Peran Serikat Pekerja Dalam Menyelesaikan Perselisihan Hubungan Industrial Pada Beberapa Studi Kasus Perusahaan - Devina Ulima Nathania Tamba; Muhamad Rizal; Sari Usih Natari (FEB Universitas Maritim Semarang, 2023)
The presence of workers in the company is dominated by executives. They often have conflicting interests for the company's activities. In order to help workers' positions remain relevant and recognized, workers need a Labor Union. In an industrial environment, it is normal for disputes to occur and the role of trade unions is needed to mediate the interests of both. Therefore, the expected goals are to explain the role of trade unions to address industrial relations disputes and the efforts that they attempt. This study determines literature review as the method by accumulating journals and collecting eight articles that meet the criteria. After having reference materials, the researcher will analyze the data based on a collection of these studies which the researcher will generalize into a literature review paper. The results of this research are that trade unions act as assistants, bodyguards, representatives, supervisors, and mediators and prioritize the settlement of disputes internally and amicably. Efforts made by trade unions include carrying out bipartite and tripartite negotiations consisting of mediation, arbitration and conciliation, as well as the industrial relations court, submitting a letter of application for Judicial Review to the Constitutional Court, and honing the skills of trade union members.